Bridging Theory and Practice: Applying Vrio and Pest to Foster Digital Transformation in Kadin Bandung City Msmes - Asmara, Maisa Azizah; Arissaputra, Rivaldi; Sabila, Sherly Nur; Arrizki, Aril Lyan (Universitas Malahayati Lampung, 2024)
ABSTRACT The data indicates that approximately 70% of MSMEs in Indonesia operate within the food and beverage sector, with 99.5% falling under the MSME classification. Despite being perceived as having numerous advantages, MSMEs face several limitations that hinder their ability to enhance competitiveness and growth. The PKM program is designed to equip participants with relevant knowledge and skills, aiming to improve product quality, expand market access, and implement effective digital strategies. The approach employed involved direct counseling and mentoring sessions for 20 women-led MSMEs supported by KADIN Bandung City. The most notable improvement was observed in participants' understanding of the benefits of digital transformation, along with a strong motivation to apply it within their business practices. Overall, the counseling and mentoring activities demonstrated their effectiveness in enhancing participants' comprehension and motivation to implement the three concepts presented in a practical business context. Keywords: PEST Analysis, VRIO Analysis, Digital Transformation